Pengaruh pemberontakan Republik Maluku Selatan terhadap kondisi sosial politik di Indonesia - Devi Putri Angelina; Lutfiah Ayundasari (Universitas Negeri Malang, 2021)
This paper is a study that discusses the rebellion of the Republic of South Maluku. This rebellion was motivated by the many former soldiers of the KNIL (Dutch Indies Colonial Army) who were disappointed with the recognition of Dutch independence to Indonesia. In addition, he did not agree with the dissolution of the NIT (State of East Indonesia) and the return of Indonesia to a unitary state. Basically, the Republic of South Maluku could not be separated from the federal system of the Indonesian state during the Dutch Military Aggression. The formation of the Republic of South Maluku was also influenced by dissatisfaction with the process of the return of the United States of Indonesia to the Unitary State of the Republic of Indonesia. In addition, it is caused by factors of the interests of certain parties such as the selfishness of a leader who does not want to step down from office and many parties who are against the discourse of a unitary state. The formation of the Republic of South Maluku greatly influenced the socio-political conditions in Indonesia, including the disruption of relations between groups in Maluku and the division of the Unitary Republic of Indonesia.Tulisan ini merupakan kajian yang membahas tentang pemberontakan Republik Maluku Selatan. Pemberontakan ini dilatar belakangi oleh kekecewaan bekas prajurit KNIL (Tentara Kolonial Hindia Belanda) dengan pengakuan kemerdekaan Belanda kepada Indonesia. Selain itu tidak setujunya atas pembubaran Negara Indonesia Timur dan kembalinya Indonesia menjadi sebuah negara kesatuan. Pada dasarnya, Republik Maluku Selatan tidak bisa dilepaskan dari sistem federal negara Indonesia pada masa Agresi Militer Belanda. Terbentuknya Republik Maluku Selatan juga dipengaruhi oleh ketidakpuasan rakyat maluku dengan proses kembalinya Republik Indonesia Serikat menjadi Negara Kesatuan Republik Indonesia. Selain itu disebabkan oleh faktor kepentingan pihak-pihak tertentu seperti keegoisan seorang pemimpin yang tidak ingin lengser dari jabatan dan banyak pihak yang kontra dengan wacana negara kesatuan. Terbentuknya Republik Maluku Selatan sangat berpengaruh terhadap kondisi sosial politik di Indonesia, meliputi hubungan antar kelompok di Maluku terganggu dan terpecahnya NKRI.